Frequenzkamm-basiertes breitbandiges MIMO-OFDM-Radar - Nuß, Benjamin (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2022)
In recent years, OFDM has become more and more important for radar applications. A disadvantage, however, is the need for high sampling rates, which is exactly the starting point of the frequency comb OFDM radar scheme. With its help, the bandwidth in the radar channel can be enhanced without increasing the sampling rates at the same time. In this way, a high range resolution can be achieved without using fast converters with high sampling rates.